2017
DOI: 10.1038/s41598-017-05196-1
|View full text |Cite
|
Sign up to set email alerts
|

3D printed scaffolds of calcium silicate-doped β-TCP synergize with co-cultured endothelial and stromal cells to promote vascularization and bone formation

Abstract: Synthetic bone scaffolds have potential application in repairing large bone defects, however, inefficient vascularization after implantation remains the major issue of graft failure. Herein, porous β-tricalcium phosphate (β-TCP) scaffolds with calcium silicate (CS) were 3D printed, and pre-seeded with co-cultured human umbilical cord vein endothelial cells (HUVECs) and human bone marrow stromal cells (hBMSCs) to construct tissue engineering scaffolds with accelerated vascularization and better bone formation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 50 publications
0
57
0
Order By: Relevance
“…β-TCP has been used primarily in synthesizing biphasic or monophasic bioceramics and α-TCP is part of many bone cements. β-TCP has been used more extensively in clinical applications of dentistry, maxillofacial surgery, tissue engineering and orthopedics than α-TCP [163][164][165] . In dental composite, TCP as a filler has been reported to increase water absorption due to the loss of minerals when it comes into contact with water, which further causes weakening of the mechanical strength of filling.…”
Section: Tcp/mcpm Based Dental Resinsmentioning
confidence: 99%
“…β-TCP has been used primarily in synthesizing biphasic or monophasic bioceramics and α-TCP is part of many bone cements. β-TCP has been used more extensively in clinical applications of dentistry, maxillofacial surgery, tissue engineering and orthopedics than α-TCP [163][164][165] . In dental composite, TCP as a filler has been reported to increase water absorption due to the loss of minerals when it comes into contact with water, which further causes weakening of the mechanical strength of filling.…”
Section: Tcp/mcpm Based Dental Resinsmentioning
confidence: 99%
“…Another promising method to increase cell adhesion and osteogenic differentiation is the modification of β-TCP with chemical substitutes, amino acid sequences or protein structures. In this context, Deng et al studied vascularization and bone formation by using β-TCP doped with different ratios of calcium silicate (CS) and co-culturing HUVECs and human BM-MSCs [ 132 ]. These experiments demonstrated that no chemical reactions occurred between both components resulting in good cell viability for 5% CS-β-TCP.…”
Section: Approaches For Creating a Bone-like Organoidmentioning
confidence: 99%
“…In conclusion, the 5% CS–β-TCP combination was biocompatible and enhanced osteogenic differentiation of human MSCs. Furthermore, HUVEC angiogenesis was stimulated as determined in vitro by tube formation as a key step of angiogenesis and in vivo by micro- Computer Tomography measurements after subcutaneous implantation in mice [ 132 ]. Due to the importance of vascularization in bone formation, Kang et al developed a vascularized bone graft by using a biomimetic cell sheet engineered periosteum and a porous β-TCP scaffold [ 133 ].…”
Section: Approaches For Creating a Bone-like Organoidmentioning
confidence: 99%
“…Among different types of 3D printing techniques, extrusion-based and inkjet-based 3D printing methods are commonly used for bioprinting. Two types of constructs are 3D printed for TE and RM: acellular scaffolds which contain biological components, and cell-laden scaffolds for tissue mimicry [ 5 ]. Biomimicry, autonomous self-assembly, and mini-tissue building blocks are the three major approaches used for 3D bioprinting.…”
Section: Introductionmentioning
confidence: 99%